Opaque minerals, magnetic properties, and paleomagnetism of the Tissint Martian meteorite. (9th August 2013) - Gattacceca, Jérôme; Hewins, Roger H.; Lorand, Jean‐Pierre; Rochette, Pierre; Lagroix, France; Cournède, Cécile; Uehara, Minoru; Pont, Sylvain; Sautter, Violaine; Scorzelli, Rosa. B.; Hombourger, Chrystel; Munayco, Pablo; et al.
Abstract: We present a description of opaque minerals, opaque mineral compositions, magnetic properties, and paleomagnetic record of the Tissint heavily shocked olivine‐phyric shergottite that fell to Earth in 2011. The magnetic mineralogy of Tissint consists of about 0.6 wt% of pyrrhotite and 0.1 wt% of low‐Ti titanomagnetite (in the range ulvöspinel 3–15 magnetite 85–97). The titanomagnetite formed on Mars by oxidation‐exsolution of ulvöspinel grains during deuteric alteration. Pyrrhotite is unusual, with respect to other shergottites, for its higher Ni content and lower Fe content. Iron deficiency is attributed by an input of regolith‐derived sulfur. This pyrrhotite has probably preserved a metastable hexagonal monosulfide solution structure blocked at temperature above 300 °C. The paleomagnetic data indicate that Tissint was magnetized following the major impact suffered by this rock while cooling at the surface of Mars from a post‐impact equilibrium temperature of approximately 310 °C in a stable magnetic field of about 2 µT of crustal origin. Tissint is too weakly magnetic to account for the observed magnetic anomalies at the Martian surface.